Early Exposure to Parents' Relationship Instability: Implications for Sexual Behavior and Depression in Adolescence - Donahue, Kelly L. (2010)
PURPOSE: Examine the effects of the timing of parents' relationship instability on adolescent sexual and mental health. METHODS: We assessed whether the timing of parents' relationship instability predicted adolescents' history of sexual partnerships and major depressive episodes. Multivariate logistic regression analyses controlled for potential mediators related to parenting and the family, including parent knowledge of activities, parent-child relationship quality, number of parents' post-separation relationship transitions, and number of available caregivers. Participants were assessed annually from age 5 through young adulthood as part of a multi-site community sample (N=585). RESULTS: Participants who experienced parents' relationship instability before age 5 were more likely to report sexual partnerships at age 16 (odds ratio [OR](adj)=1.58) or an episode of major depression during adolescence (OR(adj)=2.61). Greater parent knowledge at age 12 decreased the odds of sexual partnerships at age 16, but none of the hypothesized parenting and family variables statistically mediated the association between early instability and sexual partnerships or major depressive episode. CONCLUSIONS: These results suggest that experiencing parents' relationship instability in early childhood is associated with sexual behavior and major depression in adolescence, but these associations are not explained by the parenting and family variables included in our analyses. Limitations of the current study and implications for future research are discussed.